Intestinal obstruction due to free ileal loop radical stenosis - Grezzi, Roberto; Estefan, Alberto; Franco, Avelino (Cirugía del Uruguay, 1974)
A patient received radiotherapy as treatment cancer in the neck of the womb and a year later developed radical ileitis on free ileal loop in the form of subocclusive syndrome. The paper includes a short review of literature on its pathogeny, histopathology and treatment.